2009
DOI: 10.1007/s00595-009-3976-y
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery bypass grafting without full sternotomy

Abstract: Coronary artery bypass grafting is performed without full sternotomy in selected patients because it is less invasive. Left internal thoracic artery-left anterior descending artery bypass (LITA-LAD bypass) via a small left anterior thoracotomy is a well established procedure, which achieves good graft patency with low mortality and morbidity rates. Multiple revascularization is possible with a limited lateral thoracotomy or L-figure approach. Axillary-coronary bypass and right gastroepiploic artery-right coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…[ 39 ] While MIDCAB initially mainly encompassed the revascularisation of the LAD with the LIMA, minimally invasive techniques are not restricted to patients with single-vessel disease, but can also be applied to selected cases of MVCAD. [ 5 , 40 ]…”
mentioning
confidence: 99%
“…[ 39 ] While MIDCAB initially mainly encompassed the revascularisation of the LAD with the LIMA, minimally invasive techniques are not restricted to patients with single-vessel disease, but can also be applied to selected cases of MVCAD. [ 5 , 40 ]…”
mentioning
confidence: 99%
“…The current paradigm shift towards less invasive coronary interventions are paralleled by innovative MISCAR procedural and technological advances that comply with traditional CABG principles, graft patency, clinical outcomes and patient satisfaction (63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80). Various institutions and collaborative reports now describe innovative variations in robotic-and non-robotic MISCAR techniques, with reports that outline risk reduction strategies for safe implementation of MISCAR programs also emerging (115)(116)(117)(118)(119)(120)(121).…”
Section: New Developments In Minimally Invasive Surgical Coronary Art...mentioning
confidence: 99%
“…Off-pump coronary artery bypass surgery (OPCAB) has developed considerably over the past 15 years, 6 especially in Japan. Surveillance by the Japanese Association of Thoracic Surgery in 2007 demonstrated that the 30-day mortality rate of 65% of patients who initially underwent elective CABG as OPCAB to be 0.7%.…”
Section: Coronary Bypass Surgerymentioning
confidence: 99%